Dual Process Difference in Families Regarding Home Buying Decision - Anastasia, Njo; Narsa I, Made (Journal of Economics and Behavioral Studies, 2018)
The system of thought between rational systems and experience systems is inherent in each individual and produces different decisions. Thinking using logic tends to be used by almost every individual, but cognitive limitations make the individual simplify complex thinking to make practical decisions. This study aims to examine more in dual process on decision home buyers according to dual motives based on demographics and life cycle. Data collection was done by distributing questionnaires to selective home buyers of 235 buyers. Survey instruments include demographic and family life cycle variables. The dual process measurements using Rational-Experiential Inventory (REI-40) are designed to test individual preferences for two decision making, such as cognitive styles (rationality) and intuition (experience) using Likert scales. The results show that dual process cannot be distinguished based on dual motives. However, demographic variables such as gender, age, education, and family life cycle showed the difference in the dual process.